2019
DOI: 10.1088/1361-6668/aaf8c9
|View full text |Cite
|
Sign up to set email alerts
|

A reversible full adder using adiabatic superconductor logic

Abstract: Reversible logic circuits can perform logic operations in a thermodynamically reversible manner, or without energy dissipation. The reversible quantum-flux-parametron (RQFP) is a reversible logic gate using adiabatic superconductor logic. In the present study, we design and demonstrate a reversible full adder (RFA) using RQFP gates in order to demonstrate that RQFP gates can be used as building blocks to design reversible logic circuits. An analysis of the time evolution of the phase differences across the Jos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In a numerical simulation, we showed that the RQFP can perform logic operations in a thermodynamically reversible manner (i.e., reversible computing) in the quasi-static limit [44]. Furthermore, we have fabricated and demonstrated an RQFP gate [43] and RQFP-based reversible full adder [90]. These demonstrations indicate that the RQFP is a practical reversible logic gate and can be used as a building block for making reversible computers.…”
Section: Reversible Computermentioning
confidence: 85%
“…In a numerical simulation, we showed that the RQFP can perform logic operations in a thermodynamically reversible manner (i.e., reversible computing) in the quasi-static limit [44]. Furthermore, we have fabricated and demonstrated an RQFP gate [43] and RQFP-based reversible full adder [90]. These demonstrations indicate that the RQFP is a practical reversible logic gate and can be used as a building block for making reversible computers.…”
Section: Reversible Computermentioning
confidence: 85%
“…The development of engineering concepts working toward the realization of this principle in concrete electronic systems began in the late 1970s [71,72]. Such research has continued, albeit at a low level of intensity, to this day, yielding concrete examples of low-power digital design techniques utilizing reversible computing principles for both semiconducting [73][74][75][76] and superconducting [77] technology platforms. Estimates of the minimum energy dissipation per reversible logic operation in leading-edge Complementary metal-oxide semiconductor (CMOS) technologies extend down to the sub-attojoule (order ∼100 kT, with T ≈ 300 K) range [78].…”
Section: Reversible Computing Overviewmentioning
confidence: 99%
“…Estimates of the minimum energy dissipation per reversible logic operation in leading-edge Complementary metal-oxide semiconductor (CMOS) technologies extend down to the sub-attojoule (order ∼100 kT, with T ≈ 300 K) range [78]. But simulations of reversible superconducting circuits suggest that dissipation levels even below kT (with T = 4 K) are possible [77]. Might it be possible to approach or even breach kT dissipation levels at room temperature by using skyrmion interactions to do logic?…”
Section: Reversible Computing Overviewmentioning
confidence: 99%
“…The Reversible Quantum Flux Parametron (RQFP) logic family [71][72][73] is a logically reversible variant of the well-developed superconducting logic family AQFP (Adiabatic Quantum Flux Parametron), which has been being developed primarily at Yokohama National University in Japan. RQFP (and its not-necessarily-reversible generalization AQFP) rely on adiabatic transformation of the abstract potential energy surface (PES) that obtains within Josephson-junction-based superconducting circuits.…”
Section: Reversible Quantum Flux Parametronmentioning
confidence: 99%